Analisis Rasio Likuiditas, Solvabilitas, Dan Profitabilitas Untuk Menilai Kinerja Keuangan Pada PT. Unilever Indonesia Tbk (Unvr) Tahun 2020–2024 - Faisal Amri; Ica Ristiani; Annisa Khusnul Khotimah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the financial performance of PT Unilever Indonesia Tbk during the 2020–2024 period using liquidity, solvency, and profitability ratios as the main indicators. The research method used is descriptive quantitative with secondary data processing sourced from the company's audited annual report. The analysis instruments include the Current Ratio (CR) to measure liquidity, the Debt to Equity Ratio (DER) to measure solvency, and Return on Equity (ROE) and Net Profit Margin (NPM) to measure profitability. The results show that over the past five years, the company's liquidity has tended to be below the industry standard (in the range of 0.6–0.7), but has remained stable due to aggressive cash management efficiency. The solvency sector shows a capital structure dominated by liabilities due to a high dividend distribution policy, reflected in the significant DER figure. In terms of profitability, although net income experienced pressure in the 2021-2023 period due to rising operating costs and post-pandemic market volatility, the company demonstrated recovery through cost efficiency strategies in 2024. Overall, PT Unilever Indonesia Tbk's financial performance continues to demonstrate strong resilience thanks to market leadership and effective cost management. The results of this analysis provide investors and stakeholders with an indication that, despite the company's aggressive capital structure, its ability to generate returns from equity remains competitive. This study recommends strengthening current assets to improve liquidity resilience in the future.